Knygų leidyba Lietuvoje 1918–1940 m.: tipologinės ir teminės charakteristikos bandymas - Glosienė, Audronė (Knygotyra, 1991)
The article reviews the repertoire of books published in Lithuania in 1918–1940. Typological and subject analysis is grounded on the statistical data. The book-publishing was a dynamic process not only in a sense of the growth of its amount, but also in a sense of development of its typological and subject structure. The changes of public reading needs during the interwar period reflect in book-publishing structure. The first part of the period is characterized by small amount of book-publisсhing and prevailing not readable but practic literature: text-books, official issues. Later on the scientific literature and fiction volume has increased. The end of the period distincts by such an extent of book-publishing and variety of its typological and subject structure which enables to conclude that to that time the conditions of satisfying public manysided reading needs were formed.